Penerapan E-Big Book Rambu Lalu Lintas Berbasis Model PBL Upaya Pemahaman Membaca Simbol pada Siswa Kelas 2B SDN Wates 01 - Naila Dewi Amanati; Panca Dewi Purwati (Mathematics Education Study Program, 2025)
This study aimed to enhance comprehension of second-grade students at SDN Wates 01 about traffic sign symbols through the implementation of an interactive E-Big Book-based Problem-Based Learning (PBL) model. This study combines quantitative and qualitative methods. The results showed a significant increase in the students' average scores from 60 (48% mastery, considered fairly effective) on the pretest to 80 (83% mastery, considered very effective) on the posttest. The interactive E-Big Book and PBL-based learning design proved effective in enhancing students' learning interest, engagement, and understanding of traffic sign symbols. Observation and interviews supported the quantitative findings, with students demonstrating positive responses to the learning process. In conclusion, the combination of E-Big Book and PBL is an effective approach to improve students' comprehension of traffic sign symbols.